Crilin: CRystal calorImeter with Longitudinal InformatioN for a future Muon Collider. Issue 1 (1st November 2022) - Diociaiuti, E.; Lucchesi, D.; Paesani, D.; Pastrone, N.; Saputi, A.; Sarra, I.; Sestini, L.; Tagnani, D.
Abstract : In modern experiment, a high granularity is required in order to distinguish signal particles from background and to solve the substructures necessary for jet identification. Time of arrival measurements in the calorimeter could play an important role in HL-LHC, since a high number of pile-up collisions is expected, and the timing could be used to assign clusters to the corresponding interaction vertex. In a Muon Collider, the timing could be used to remove signals produced by beam-induced background, asynchronous with respect to the bunch crossing. The calorimeter energy resolution is also fundamental to measure the kinematic properties of jets: a finely segmented calorimeter design should be favored in order to solve the jet substructure. However, this contrasts with the requirement for high timing resolution even for signal events involving low energy deposits, such as in the case of high impulse muons. Our proposed design, the Crilin calorimeter, is a semi-homogeneous calorimeter based on Lead Fluoride (PbF2 ) Crystals readout by surface-mount UV-extended Silicon Photomultipliers (SiPMs). In this paper, the development of a small prototype consisting of 2 layers of 3 × 3 crystals each is reported along with the relative results.